A retrospective study on the artificial mummification of the Blessed Andrea da Montereale (AD 1479) - Ventura, Luca; Traversari, Mirko; Sabatini, Noemi; Cilli, Elisabetta; Telera, Giacomo; Ripani, Maurizio (Medicina Historica, 2022)
Andrea da Montereale was a 15th Century Augustinian monk from the inner Abruzzo region, central Italy. We investigated the preservation mechanisms of his body by retrospective survey of textual sources and reports from the Canonical Recognitions. The partially mummified body of the Blessed Andrea da Montereale revealed indisputable evidence of artificial mummification (excerebration and evisceration cuts, absence of internal organs) at visual inspection. The cadaver features emphasized by the hagiographers (vivid colors, absence of putrefaction or bad smelling for thirty days after death, without balsams treatments) sounds like an unrequested explanation for the body miraculous preservation. To the best of our knowledge, this represents the twelfth known case of an embalmed body in Catholic Religion, the tenth in Central Italy, and the second one documented in the Abruzzo region.